2019
DOI: 10.33263/briac94.183186
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of broiler chicken meat after the combined use of antibiotic and oak bark extract

Abstract: With the increase in consumption of poultry products, the requirements for their quality, especially for nutritional and biological value, also increased. As the experience and scientific achievements of recent years shows, these indicators are quite manageable, that is, you can create products with predetermined properties. The aim was to study the combined use of chlortetracycline and Quercus cortex extract. The quantitative ratios of lipids and fatty acids in poultry meat are the main criteria of its qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Furthermore, patients with metabolic disorders such as hypertension, arthritis, and diabetes may prefer chicken meat over red meat as it contains less fat. However, investigations have indicated that the fast-growing breeds of chicken have increased fat content, particularly if they are grown indoors and for commercial purposes [1]. The breast meat of the slow-growing chickens contained more protein and α-tocopherol than the fast-growing chickens and half the amount of fat [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with metabolic disorders such as hypertension, arthritis, and diabetes may prefer chicken meat over red meat as it contains less fat. However, investigations have indicated that the fast-growing breeds of chicken have increased fat content, particularly if they are grown indoors and for commercial purposes [1]. The breast meat of the slow-growing chickens contained more protein and α-tocopherol than the fast-growing chickens and half the amount of fat [2].…”
Section: Introductionmentioning
confidence: 99%